The Growing Importance of Development Diplomacy - Kharel, Hemanta (NCWA Annual Journal, 2023)
In recent times, development diplomacy has received the highest priority in international relations. It is mostly conducted through multilateral activities on a global, regional, and bilateral level, including cooperation from the United Nations and its specialized agencies. There are both opportunities and risks in development diplomacy. Therefore, it should be conducted very cautiously and efficiently. Even despite collective efforts internally and externally, Nepal is still lagging to make notable progress in the development arena with an adverse effect on the living standard and welfare of the people. There is a common understanding and consensus among the experts that Nepal should act simultaneously to receive foreign assistance in national priority areas through proper development diplomacy and attract foreign direct investment to increase national production by focusing on export-led economy. For effective conduct of development diplomacy, basic elements such as proven competence, skillful negotiation, good quality of public communications, knowledge about cultural and social aspects, and ample experience to manage public affairs are required. The personnel working in Nepal's diplomatic missions abroad need to be professionally trained and intellectually equipped.